2021
DOI: 10.1001/jamapediatrics.2021.0775
|View full text |Cite
|
Sign up to set email alerts
|

Delivery Room Interventions for Hypothermia in Preterm Neonates

Abstract: IMPORTANCE Prevention of hypothermia in the delivery room is a cost-effective, high-impact intervention to reduce neonatal mortality, especially in preterm neonates. Several interventions for preventing hypothermia in the delivery room exist, of which the most beneficial is currently unknown. OBJECTIVE To identify the delivery room thermal care intervention that can best reduce neonatal hypothermia and improve clinical outcomes for preterm neonates born at 36 weeks' gestation or less.DATA SOURCES MEDLINE, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 66 publications
(192 reference statements)
0
28
0
2
Order By: Relevance
“…Abiramalatha et al performed a systematic review and network meta‐analysis of delivery room interventions to prevent hypothermia in preterm infants. The researchers found that relative to routine care, use of a plastic bag or wrap was associated with a greater core temperature whether alone (mean difference [95% confidence interval] = 0.56 [0.44–0.69]°C) or combined with a thermal mattress (0.98 [0.60–1.36]°C), heated humidified inhaled air (0.76 [0.38–1.15]°C) or a plastic skullcap (0.62 [0.37–0.88]°C) 29 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abiramalatha et al performed a systematic review and network meta‐analysis of delivery room interventions to prevent hypothermia in preterm infants. The researchers found that relative to routine care, use of a plastic bag or wrap was associated with a greater core temperature whether alone (mean difference [95% confidence interval] = 0.56 [0.44–0.69]°C) or combined with a thermal mattress (0.98 [0.60–1.36]°C), heated humidified inhaled air (0.76 [0.38–1.15]°C) or a plastic skullcap (0.62 [0.37–0.88]°C) 29 …”
Section: Resultsmentioning
confidence: 99%
“…In the subpopulation of preterm infants <28 weeks of gestation the effect was even greater: 24 of the 35 (69%) infants receiving heated, humidified gases were normothermic, compared with 16 of the 38 (42%) infants in the group control ( p = 0.03) 45 . In a network meta‐analysis of delivery room interventions designed to prevent hypothermia in preterm infants, Abiramalatha et al found that the combination of a plastic bag or wrap with heated, humidified gases was associated with a greater core temperature than for routine care, with mean difference [95% CI] = 0.76 [0.38–1.15]°C 29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Although the plastic bag or wrap with thermal mattress provided the greatest improvement for core body temperature as well as a trend with decreased mortality, it was associated with an increased risk of hyperthermia, which the authors suggest may not be the optimal first-line modality. 5 Importantly, plastic bag or wrap with heated humidified gas was associated with a decrease in major brain injury and mortality. 5 This systematic review and metaanalysis has multiple limitations.…”
Section: Commentarymentioning
confidence: 99%
“…5 Importantly, plastic bag or wrap with heated humidified gas was associated with a decrease in major brain injury and mortality. 5 This systematic review and metaanalysis has multiple limitations. cap.…”
Section: Commentarymentioning
confidence: 99%